New species of bristletails of the family Machilidae (Microcoryphia) from caves in Abkhazia and Ukraine - Kaplin, Vladimir; Vargovitsh, Robert S. (Zootaxa, 2020)
Two new species of bristletails of the family Machilidae are described from caves in the Western Caucasus (troglophile Coryphophthalmus troglophilus sp. nov.) and in the Eastern Carpathians (trogloxene Trigoniophthalmus ukrainensis sp. nov.). The main morphological adaptations of C. troglophilus sp. nov. to life in caves include green eye color; weak body pigmentation; well-developed arolium and claws; relatively long cerci, tarsae and tibiae of the hind legs; long apical needles of the urostyli; large sublateral spines on urocoxites IX. C. troglophilus sp. nov. resembles C. abchasicus (Kaplin, 2017), but they are distinguishable in color of eyes, ratio of eye contact to length, length of cerci, structures of the labial palps, legs, urocoxites IX, ovipositor, and parameres. Trigoniophthalmus ukrainensis sp. nov. has no recognized morphological adaptations to life in caves. This species resembles T. alternatus (Silvestri, 1910), but they are easily distinguished in the number of annuli in distal chains of flagellum, ratio of width to length of paired ocelli, chaetotaxy of male maxillary and labial palps.